Sustainability Disclosure in Financial Statements - Regulations and Issues - Bacheva, Snejana; Pozharevska, Rumiana (Research Papers, 2024)
In recent years, the efforts of governments and institutions have focused on creating an economy that benefits people and the environment. At the same time, businesses are exposed directly or through third parties, such as suppliers and customers, to significant risk from climate change. Investors need consistent, complete, comparable and verifiable information to assess how climate-related risks and opportunities affect the financial health of businesses, including their future cash flows and value. The latter gives rise to the need to create a regulatory framework that will determine the requirements for identifying, measuring and disclosing the risks and opportunities of enterprises. Accountants and auditors face new challenges related to appropriate disclosure of these issues. Since the adoption of the Paris Agreement in 2015, a number of measures have been taken to strengthen the sustainability reporting requirements of companies and increase their responsibilities. In recent years, environmental, social and corporate governance (ESG) reporting has been considered a key component to successfully addressing climate change.The article aims to analyze the processes related to the regulation and reporting of information by enterprises on climate and sustainability issues. To achieve the goal, the following tasks are set: to outline the role of institutions at the European and global level for creating sustainability standards; to present the disclosure recommendations to the enterprises; to define the features of standardization and its impact on financial statements and the development of the accounting profession in the future.